Dengue: Randomized multicenter studies are needed with medicines that could be effective as a second indication - Accinelli, Roberto Alfonso (2024)
Dengue is the most common vector-borne viral disease, with low fatality rate, one death per 1000 patients. Its treatment consists of hydration, rest and symptomatic treatment. Doxycycline interferes with the entry into human cells, by inhibiting the changing E protein configuration, and stopping its replication by acting on the NS2BNS3pro protease of the virus. Therefore, itcould be an alternative, and when the disease has reached the stage of cytokine storm, manifested by severe thrombocytopenia, hemoconcentration and systemic involvement, the use of steroid or immunoglobulin pulses could be indicated. Multicenter placebocontrolled studies are needed to demonstrate the effect of these drugs in secondary indication so that the WHO and CDC can recommend or not their use, so for now we cannot use them.